Urban water sustainability constructing infrastructure for cities and nature - Bell, Sarah (Earthscan Studies in Water Resource Management, 2018)
This book investigates the implications of different developments in water technology and infrastructure for urban sustainability and the relationship between cities and nature. The main purpose of the book is to draw out the social, political and ethical implications of technical changes that are occuring in urban water systems around the world, with positive and negative impacts on sustainability.